Does Social Media Selectively Transform the Protest Paradigm? Evidence from Online News and X Posts During Indonesia’s 2025 Demonstrations - Eriyanto (Language, Technology, and Social Media, 2026)
This study examines how the protest paradigm operates in Indonesia’s hybrid media ecosystem by comparing online news coverage and social media posts during the August–September 2025 demonstrations. Using quantitative content analysis, this study analyzed 2,682 Detik.com news articles and 421 posts from the X account @barengwarga published between 25 August and 5 September 2025. The analysis focused on three dimensions: protest framing, sourcing patterns, and marginalization/legitimization devices, with differences between media types tested using chi-square analysis. The findings show that the protest paradigm is transformed selectively rather than uniformly. Riot and confrontation frames appeared at comparable levels in online news and social media, indicating the persistence of conflict-oriented protest representation. However, social media more frequently used spectacle and debate frames, foregrounded protesters’ voices, highlighted police violence, and represented protests as peaceful. In contrast, online news relied more heavily on institutional sources and more often associated protesters with violence. These statistically significant differences indicate that social media do not fully overturn the protest paradigm but reconfigure it by shifting narrative authority and moral attribution. This study contributes to protest communication scholarship by offering empirical evidence from a Global South hybrid media context.